Conservative management of an unusual bilioduodenal fistula post laparoscopic Duodeno-Ileal Switch (SADI-S) case report. (2017) - Chelala, E.; Adam, E.; Rizk, A.; Makhoul, E.
Highlights: A bilioduodenal fistula may rarely occur after duodenal switch. This case report is original and interesting showing a successful conservative management of this rare complication. A review of the literature on different types of Internal Biliodigestive Fistulae and their appropriate management are reported and briefly discussed. We highlight the differential diagnosis and optional treatment in such a rare complication, and how we succeeded in its conservative management. An accurate diagnosis and a team work between gastroenterologists and surgeons may be salvatory in this type of complication. Abstract: Introduction: Single anastomosis duodeno-ileal bypass with sleeve gastrectomy (SADI-S) is an advanced operation for morbid obesity. To our knowledge, no internal Biliodigestive Fistula has yet been reported as specific complication in the field of metabolic and bariatric Biliopancreatic diversion. Case presentation: In this case report, we detail the case of a 57-year-old man who underwent a Single Anastomosis Duodeno-Ileal Switch (SADI-S) bariatric procedure for morbid obesity. Upon admission 3 weeks after the SADI-S procedure acute sepsis caused by a delayed choledoco-duodenal Fistula was diagnosed. A conservative management of this rare complication was successful. Discussion: We highlight the differential diagnosis and optional treatment in such a rare complication, and how we succeeded in its conservative management, without any need for endoscopic nor surgical intervention. A review of the literature on different types of Internal Biliodigestive Fistulae and their appropriate management are reported and briefly discussed. Conclusion: The aim of this case report is to highlight the existence of such a rare complication, and its successful multidisciplinary conservative medical management.